Oil Price Uncertainty and Sectoral Stock Returns in China: A Time-Varying Approach - Guglielmo Maria Caporale; Faek Menla Ali; Nicola Spagnolo (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper investigates the time-varying impact of oil price uncertainty on stock prices in China using weekly data on ten sectoral indices over the period January 1997-Febraury 2014. The estimation of a bivariate VAR-GARCH-in-mean model suggests that oil price volatility affects stock returns positively during periods characterised by demand-side shocks in all cases except the Consumer Services, Financials, and Oil and Gas sectors. The latter two sectors are found to exhibit a negative response to oil price uncertainty during periods with supply-side shocks instead. By contrast, the impact of oil price uncertainty appears to be insignificant during periods with precautionary demand shocks.
Keywords: C32; Q43; 330; China; oil price uncertainty; sectoral stock returns